2021
DOI: 10.29333/iji.2021.14259a
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Verbal Positive Reinforcement of Teachers during School from Home in the Covid-19 Pandemic Era

Abstract: During school from home, students need positive reinforcement both from parents and teachers to improve or trigger their positive behavior. This study aimed to identify the intensity of verbal positive reinforcement given by teachers to students during school from home. It was a mix-method study by involving 310 elementary school teachers as respondents (41.29 % males, 58.71% females). The intensity of positive reinforcement was measured using an instrument developed from the basic theory of positive reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
5
0
2
Order By: Relevance
“…Nevertheless, some teachers were still able to carry out positive communication practices by applying language politeness. This is in line with the results of other studies, showing that some teachers were more likely to provide students with verbal positive reinforcement based on the language politeness theory despite online learning (Mantasiah et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, some teachers were still able to carry out positive communication practices by applying language politeness. This is in line with the results of other studies, showing that some teachers were more likely to provide students with verbal positive reinforcement based on the language politeness theory despite online learning (Mantasiah et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…It is likely that the low use of language politeness for communication is a result of the low intensity of direct communication between teachers and students. Mantasiah, Yusri, Sinring and Aryani. (2021) found that during online learning, teachers used WhatsApp more frequently as the main media to deliver the lessons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second study conducted by Mantasiah (2021), published in the International Journal of Instruction (IJI) (Scopus Q2), focused on teachers. This study concludes that during home learning:…”
Section: Problems With the Implementation Of Online Learning Policies...mentioning
confidence: 99%
“…Ada enam prinsip yang mesti diperhatikan guru saat memberikan penguatan positif yaitu tulus, antusias, meaningfulness, hindari respon negatif, segera berikan, dan berikan secara beragam (Mantasiah, et al, 2021). Tulus berarti penguatan positif diberikan berdasar apa yang dirasakan atau dipikirkan guru, tidak berpura-pura.…”
Section: Penguatan Positifunclassified